Menguatkan Nilai Sosial dan Kesadaran Lingkungan dalam Pembelajaran IPS SD melalui Kampanye Ecobrick: Studi Kasus di SDN Tanggultlare, Jepara - Rosyidah Rosyidah; Muhammad Fashihullisan; Erik Aditia Ismaya (Pusat Riset dan Inovasi Nasional, 2025)
Plastic waste is one of the most pressing environmental issues in Indonesia's coastal areas, including in Jepara. This study aims to describe how project-based and contextual Social Sciences (IPS) learning can strengthen social values and environmental awareness through ecobrick campaigns by 6th grade students of SDN Tanggultlare. This study uses a qualitative approach with a case study method, involving five students as the main subject, and a classroom teacher as a supporting informant. Data collection techniques include observation, semi-structured interviews, and visual documentation. The results of the study show that ecobrick campaign activities are collectively able to foster the value of responsibility, mutual cooperation, environmental concern, and effective communication between students. These findings confirm that social studies learning based on real action and local contexts can be a means of internalizing meaningful social values at the elementary school level.